2019
DOI: 10.21595/jve.2019.20427
|View full text |Cite
|
Sign up to set email alerts
|

Natural frequency sensitivity and influence analysis of TBM cutterhead system

Abstract: TBM cutterhead works in complex working conditions, which endures the reverse impact forces of rock breakage, resulting in parts abnormal failure. Hence, the study of the system inherent characteristics is the basis for cutterhead dynamic design. Based on the established vibration model of a TBM split-cutterhead system, the modal method is used in the dynamic model and the natural frequency sensitivity expressions to system parameters are deduced. Then a cutterhead system of a water conservancy project in Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Studies have shown that it is feasible to utilize vibration monitoring and oil analysis techniques for the condition monitoring and fault diagnosis of key components such as main bearings and gearboxes [95,96]. Moreover, vibration during tunnel excavation is considered to have a significant impact on the performance of a tunnel boring machine, especially its excavation efficiency [70,97,98]. Zhu et al [99] proposed a comprehensive performance evaluation method for the cutterhead by using the root-mean-square value of the speed as the vibration strength index.…”
Section: Identifying Equipment Faultsmentioning
confidence: 99%
“…Studies have shown that it is feasible to utilize vibration monitoring and oil analysis techniques for the condition monitoring and fault diagnosis of key components such as main bearings and gearboxes [95,96]. Moreover, vibration during tunnel excavation is considered to have a significant impact on the performance of a tunnel boring machine, especially its excavation efficiency [70,97,98]. Zhu et al [99] proposed a comprehensive performance evaluation method for the cutterhead by using the root-mean-square value of the speed as the vibration strength index.…”
Section: Identifying Equipment Faultsmentioning
confidence: 99%